Procedimiento administrativo en materia ambiental relacionada con la responsabilidad objetiva por daños ambientales - Goya García, Joffre Joel (2024)
The Ecuadorian Constitution recognizes the vulnerability of the environment and, for this reason, grants nature the status of subject of law. The objective of this study was to analyze the administrative procedure related to objective liability for environmental damages. The methodology was mixed approach and descriptive scope. The sample was made up of 3 lawyers specializing in environmental matters and 40 lawyers. The survey and interview were used as techniques. The results showed that the evolution of the legal foundations since 2008 stands out, recognizing the protection of nature as a subject of law. The administrative procedure to prevent environmental damage is considered effective, although the need to improve the agility and efficiency of the procedures is noted. The reversal of the burden of proof is supported to allow companies to prove their innocence. Although progress is seen in environmental law, the complexity of determining objective liability is highlighted. It is concluded that there is a diversity of opinions in Guayaquil on this issue, highlighting the importance of preserving the right to defense and improving the agility of procedures.